Studi Kandungan Kimia Ekstrak Buah Pakoba Merah (Syzygium sp) - Jenny Kumajas; Dian Herlinda Octorina Howan (Jurnal Kimia Fullerene, 2018)
Red Pakoba (Syzygium sp) is a plant endemic to North Sulawesi. This study aims to find secondary metabolites from red pakoba fruit extract (Syzygium sp). The process is carried out by extraction and phytochemical testingFrom the phytochemical filtration results obtained the extract of red Pakoba fruit contains phenol compounds, terpenes, steroids and flavonoids. It needs further investigation the activity and the structure of the active compound from red pakoba fruit extract.